Modification of palm kernel oil structure with fatty acid distillate of rice bran oil in an enzymatic fixed-bed mini-reactor - Nattee Akkarawatkhoosith (2022)
This work proposed the effective process to modify the structure of palm kernel oil (PKO) for improving the melting point. In this process, lauric acid can also be obtained as a valuable by-product. The low-value rice bran oil fatty acid distillate (RBOFAD) was applied as an acyl donor which was carried out in an enzymatic (Lipozyme TL IM) fixed-bed mini-reactor. The influence of operating conditions including reaction temperature (50–70 °C) and residence time (9–65 min) on the degree of incorporation was investigated. The results indicated that the extraction of lauric acid from the modified PKO was achieved; however, the melting point was not significantly improved. The pretreatment of RBOFAD prior to interesterification was successfully applied to improve the melting point of the structured PKO as well as to extract the lauric acid. Main and interaction effects involving reaction temperature (50–70 °C), residence time (10–30 min), and RBOFAD:PKO volumetric ratio (3:1–9:1) on the melting point were examined and optimized based on the response surface methodology. Maximum melting point of 32.5 °C and 13 wt% of lauric acid (based on the initial amount of PKO) were achieved at the residence time of 10 min, RBOFAD-to-PKO volumetric ratio of 9:1, and the reraction temperature of 50 °C.